The value of Fast Dixon combined with deep learning technology in contrast agent-free high-resolution magnetic resonance imaging of the brachial plexus - Xie, Si; Du, Xuehui; Zhang, Zhitao; Chen, Guangxiang (Frontiers in Neurology, 2025)
IntroductionThis study aimed to investigate the application of Fast Dixon combined with the deep resolve gain (DRG) technique for enhancing the image quality of the brachial plexus on high-resolution MRI without the use of contrast agents.MethodsHeavily T2–weighted Fast Dixon high-resolution coronal thin-slice magnetic resonance imaging was conducted on 19 social volunteers. Post-scan, the original data underwent reconstruction using deep learning-based denoising technology. Subjective quality scores were assigned to both the original and MIP images, and those processed with and without denoising technology were compared. The signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) values for each segment of the bilateral brachial plexus were measured and analyzed to assess image quality.ResultsSubjective evaluations revealed that the quality of both original thin-slice and thin-MIP images processed with the DRG significantly outperformed those processed without the DRG (original thin-slice p = 0.005, thin-MIP p < 0.05). The bilateral SNRs and CNRs of each anatomical structure (root, trunk, cord, branch) of the brachial plexus in the experimental group with DRG were significantly greater than those in the control group without DRG (p < 0.05), as follows: the SNRs of the bilateral nerve roots increased by 35.1–36.2%, the SNRs of the bilateral nerve trunks increased by 40.6–40.8%, and the SNRs of the bilateral nerve cords and branches increased by about 40–45%. The CNR of the bilateral nerve roots increased by 43.1–44.6%, the CNR of the bilateral nerve trunks increased by 41.8–41.7%, and the CNR of the bilateral nerve cords and branches increased by 47.3–50.6% (root p < 0.001, trunk p < 0.001, cord p = 0.001, branch p = 0.011).ConclusionFast Dixon T2WI can enhance the visibility of brachial plexus segments to a certain extent through DRG denoising technology, which may be an effective means to visualize the brachial plexus without contrast agent.